Properties of core specimens according to core diameter and coarse aggregate volume - Lee, Jeonho; Lee, Jeongtaek; Jeon, Eunyeong; Lee, Sangsoo (Edelweiss Applied Science and Technology, 2024)
Among methods for safety diagnosis of concrete, estimation of the compressive strength using core specimens, despite excellent accuracy, is less preferred than non-destructive testing methods due to a number of problems. Therefore, the object of the present study is to produce basic data for estimation of small-diameter core specimens by analyzing the ratio of compressive strength versus core specimen diameter, and analyzing the correlations between coarse aggregate volume and ultrasonic pulse velocity. Results showed that the compressive strength tends to decrease as the diameter of the core specimen decreases, and that the ultrasonic pulse velocity tends to increase with the coarse aggregate volume.